101k views
0 votes
What is the solution to -2(4x+3)=5+3x

i really need it now
and can you show me how it's done

User Cdoublev
by
4.9k points

2 Answers

3 votes

-2(4x+3)= 5+3x

mutiply the bracket by -2

(-2)(4x)= -8x

(-2)(+3)= -6

-8x-6= 5+3x

move 3x to the other side

sign changes from +3x to -3x

-8x-3x-6= 5+3x-3x

-11x-6= 5

move -6 to the other side

-11x-6+6= 5+6

-11x= 11

divide both sides by -11

to get x by itself

to get positive x

-11x/-11= 11/-11

answer:

x= -1

User Vojtam
by
4.3k points
5 votes
Distributive Property of Equality

-2(4x+3)=5+3x
-8x-6=5+3x
-8x=11+3x
-11x=11
x=-1
User Romanzdk
by
4.9k points